Surface and wear mechanisms analysis of phosphorous-free and conventional engine lubricants on cylinder liner and piston rings surfaces - Ozkan, Dogus; Kaleli, Hakan; Berthier, Yves; Yuksek, Levent (EMERALD GROUP PUBLISHING LIMITED, 2015)
Purpose - This paper aims to investigate the wear mechanisms, formations and effectiveness of tribofilms of new developed, antiwear additive which is called mercapthocarboxylate. The mercapthocarboxylate is a sulphur-based and non-phosphorus additive. Design/methodology/approach - The effectiveness of the additive was examined through a set of laboratory endurance tests that applied with single cylinder spark ignition engine. Two types of lubricants were used to compare the engine tests which were thiophosphate (ZDDP) containing engine lubricant (phosphorus containing) and mercapthocarboxylate containing non-phosphorus and non-ash crankcase oil. Lubricants were tested under identical operating conditions for 100 hrs. The surfaces of cylinder liner and piston rings were inspected through optical microscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy techniques. Findings - Catalysis-friendly and sulphur-based mercapthocarboxylate additive can be an alternative antiwear additive package for lubrication oil due to better wear performance when compared to ZDDP. Originality/value - Sulphur-based mercapthocarboxylate is a new developed antiwear additive and was applied to lubrication oil in this study. This lubrication oil was tested in the real engine environment by using 100-hr engine bench tests.
Keywords: Additives; Wear; Lubricating oils; Microscopy; Spectroscopy; Sliding surfaces; Cylinder liner; Piston rings; CATALYST DEACTIVATION; Engineering